Presence of Perfluoroalkyl Carboxylic Acids and Sulfonates in Vietnamese Food Contact Materials - Minh, Phan Dang; Anh, Hoang Quoc; Lieu, Tran Thi; Quang, Phan Dinh; Nghia, Nguyen Trong; Chuc, Nguyen Thi; Huong, Nguyen Thi Anh; Tuyen, Le Huu; Thi Quynh Hoa, Nguyen (VNU Journal of Science: Earth and Environmental Sciences, 2023)
Per- and polyfluoroalkyl substances (PFASs) are considered as persistent organic pollutants (POPs), which should be restricted or eliminated. In this study, concentrations of four perfluoroalkyl carboxylic acids (perfluorobutanoic acid PFBA, perfluorohexanoic acid PFHxA, perfluorooctanoic acid PFOA, perfluorodecanoic acid PFDA) and four perfluoroalkyl sulfonates (perfluorobutane sulfonate PFBS, perfluorohexane sulfonate PFHxS, perfluorooctane sulfonate PFOS, perfluorodecane sulfonate PFDS) were analyzed in food contact materials (FCM) collected from Hanoi, Vietnam. A total of 15 FCM samples was obtained including several categories such as instant drink/food boxes, bags, cups, wrappers, and tray. The FCM samples were untrasonic extracted with methanol, concentrated, and filtered before analysis by a liquid chromatography–tandem mass spectrometry (LC-MS/MS) system. Recoveries of native and surrogate standards ranged from 70% to 130% with RSD < 20% in replicated analysis. Method detection limits of PFASs ranged from 0.04 to 0.08 ng/g. Concentrations of S8PFASs ranged from not detected (ND) to 1.46 (average ± SD: 0.417 ± 0.479) ng/g. Detection frequencies of PFASs decreased in the order: PFDA (33%) > PFBA, PFOA, PFHxS, PFOS (27%) > PFDS (13%) > PFHxA (7%) > PFBS (0%). Average concentrations of individual compounds decreased in the order: PFOS > PFDA > PFHxS > PFOA > PFBA > PFHxA > PFDS > PFBS. Relatively low PFAS concentrations found in the FCM samples of this study indicated that these substances were mainly derived from unintentional sources rather than intentionally added to the materials.